Uji Aktivitas Ekstrak Etanol Kapulaga (Amomum compactum) sebagai Penghambat Pertumbuhan Candida albicans - Marda Hamelya Putri; Khoirul Rista Abidin; Khairul Bariyah; Puspa Amalia (Bahiraliya Natura Science, 2025)
This study aimed to evaluate the antifungal effectiveness of ethanol extract of cardamom against Candida albicans. The well diffusion method was used with extract concentrations of 5%, 10%, and 15%, alongside a positive control (ketoconazole). The inhibition zone was measured to assess antifungal activity. The 15% extract concentration produced an average inhibition zone of 16.56 ± 0.86 mm, categorized as moderate inhibition. These findings suggest that A. compactum possesses antifungal potential due to its bioactive compounds, such as flavonoids and tannins, which are known for their antimicrobial properties. The growing resistance of Candida albicans to synthetic antifungal agents highlights the importance of exploring natural alternatives. Hence, A. compactum extract demonstrates promising potential as a natural antifungal candidate that could be further developed for pharmaceutical or herbal formulations. The 15% ethanol extract of A. compactum exhibited measurable inhibitory activity against Candida albicans, with inhibition zones of 16.7 mm, 17.65 mm, 16.3 mm, and 15.6 mm across four replications. The mean inhibition zone was 16.56 mm with a standard deviation of 0.86 mm, indicating moderate antifungal strength. The variation among replicates was within the expected range for microbiological assays and may result from minor differences in extract diffusion or fungal growth conditions.